Fiscal Rules and Discretion in a World Economy - Halac, Marina; Yared, Pierre (American Economic Review, 2018)
Governments are present-biased toward spending. Fiscal rules are deficit limits that trade off commitment to not overspend and flexibility to react to shocks. We compare coordinated rules, chosen jointly by a group of countries, to uncoordinated rules. If governments’ present bias is small, coordinated rules are tighter than uncoordinated rules: individual countries do not internalize the redistributive effect of interest rates. However, if the bias is large, coordinated rules are slacker: countries do not internalize the disciplining effect of interest rates. Surplus limits enhance welfare, and increased savings by some countries or outside economies can hurt the rest. (JEL D82, E43, E62, H62)